Knowledge creation by student leaders to promote their own leadership development: Amulti-university social dream-drawing project (Journal of Student Affairs in Africa, 2024)
Engaging student leaders in knowledge creation in support of their own leadership development is an important strategy in the scholarship of integration which seeks to promote research-based, student engaged professional practices. This article describes a strategy for engaging student leaders in support of such development, drawing on the insights they gained from their own leadership experiences. South African student leaders participated in a multi-university, social dream-drawing study which was designed using a socio-analytical framework. Through this project, leade rship experiences were made manifest at unconscious and conscious levels. Group sharing and reflection helped the participants recognise and process their leadership experiences, and to uncover and explore areas that needed development. Engaging in knowledge creation about their own development, the participating students co-produced an evidence-based understanding of the importance of integrated approaches about the development of student leadership. In addition, their participation in a process of compassionate engagement positioned them as co-developers of problem-solving insights in support of their own development and, more broadly, universities’ social and cultural capabilities. Pule and Gibney (2023) also demonstrated this. The social dream-drawing findings furthermore indicated how such interventions could go beyond an examination of the perspectives of individual leaders to consideration of the nature of student leadership as a group, organizational or even societal function – considering intra- and inter-group dynamics; different organizational levels and their leadership sub-systems; and the role of student leadership in society at large. In addition, the research conducted through social dream-drawing may be seen as strengthening the argument for the broader adoption of the scholarship of integration in pursuit of strategic goals.
Keywords: co-productive; research; leadership; student-engagement practices; student development; scholarship of integration; social dreaming